para real funcao definida por f (x)=x2+2×-3, obtenha f (5), f (0), f (-3)
Soluções para a tarefa
Respondido por
0
Resposta:
Explicação passo-a-passo:
f (5) = (5) 2 + 2 (5) - 3= 17
f ( 0) = 2+2-3= 1
f (-3) = (-3) 2 + 2 (3) -3 = -1
Respondido por
0
Resposta: F(5)= 4
F(0)= -6
F(-3)= 12
Explicação passo-a-passo:
Primeiro: respondendo a f(5)
F(5)= 5×2+2×(-3)=
F(5)= 10+(-6)=
F(5)= 10-6=
F(5)= +4
Respondendo à f(0)
F(0)= 0×2+2×(-3)=
F(0)= 2×(-3)=
F(0)= -6
Respondendo à f(-3)
F(-3)= -3×2+2×(-3)=
F(-3)= -6+2×(-3)=
F(-3)= -4×(-3)=
F(-3)= 12
Perguntas interessantes